Factors Associated with Low Back Pain Among Pregnant Women in Padang, West Sumatra - Rahmatul Ulfa; Siti Yuliharni; Yanti Puspita Sari (NERS Jurnal Keperawatan, 2026)
Although low back pain is a common musculoskeletal complaint among pregnant women and is known to negatively affect their quality of life and daily activities, evidence regarding the factors influencing this condition remains limited. Therefore, this study aims to identify the factors associated with low back pain among pregnant women. This study used a cross-sectional study involved 111 pregnant women was selected using consecutive sampling at the Belimbing Public Health Center, Padang, West Sumatra. Data were collected through self-administered demographic questionnaire, Pregnancy Physical Activity Questionnaire (PPAQ), and the Roland Morris Disability Questionnaire (RMDQ), and BMI measurements. The results showed that the average low back pain score was 9.71, ranging from 3 to 20. Based on bivariate analysis using the Mann Whitney test, Kruskall Wallis test, and Spearman rank, it was found that there was a relationship between maternal age (p=0.002), gestational age (p=0.017), parity (p<0.001) with low back pain. Weight gain and physical activity were not related to low back pain, with (p=0.062) and (p=0.140), respectively. Low back pain in pregnant women is associated with maternal age, gestational age, and parity, whereas physical activity and body weight do not appear to have a significant relationship. Targeted education and simple preventive strategies may help reduce lower back pain during pregnancy.